The Importance of Learning Visual Literacy or “The Day Angela Merkel Didn’t Know Where Germany is Situated”of Learning Visual Literacy or “The Day Angela Merkel Didn’t Know Where Germany is Situated” - Reis, Ricardo (2018)
This text, as an essay, gives a set of examples that, in my opinion, reflect the importance of learning visual literacy, not so much as a simple visual language domain, supposedly universal, but as a visual literacy connected with the observer and the sociocultural context wherein the images (and other visual material) are produced, distributed and consumed. This perspective requires a deep educational change in order to allow students to mobilize, in their daily life, a set of knowledge built through the understanding of the images and varied visual information, when they are put in the context.